Influence of Deformation Temperature and Strain Rate on Martensitic Transformation of Duplex Stainless Steel and Its Corresponding Kinetic Model - Qiyong Zhu; Fei Gao; Zilong Gao; Weina Zhang; Shuai Tang; Xiaohui Cai; Zhenyu Liu (Metals, 2025)
For investigating the effect of temperature and strain rate on martensitic transformation and establishing the corresponding kinetic model for newly TRIP (transformation-induced plasticity) aided duplex stainless steel (DSS), the tensile tests are conducted at temperatures of 20–150 °C and strain rates of 0.0001–150 s−1. The stepped cross-section tensile specimen is proposed and designed for obtaining microstructure at specific strain during dynamic tensile testing. The results demonstrate that the deformation mechanism of austenite in TRIP-aided DSS is highly sensitive to temperature and strain rate. As the deformation temperature increases, strain-induced martensitic transformation is inhibited, and the deformation mechanism transforms from martensitic transformation to the co-occurrence of martensitic transformation and twinning, and finally, twinning is the main deformation mechanism. This leads to reduced strength with an initial increase followed by a decrease in elongation. As the strain rate increases, martensitic transformation is inhibited, resulting in a reduction in strength and plasticity during quasi-static tensile testing, while during dynamic tensile testing, strength increases due to enhanced resistance to dislocation motion, and plasticity displays no significant variation because of the combination of adiabatic softening and martensitic transformation suppression. Moreover, during tensile deformation, a plastic temperature rise model is established for newly developed DSSs. Based on this model, the Ludwigson–Berger model for martensitic transformation was modified to couple the effect of temperature and strain rate by considering the non-uniform distribution of temperature rise within the material and its variation with strain rate, as well as the suppression of dynamic strain rate on martensitic transformation. This new model could accurately describe the characteristics of martensitic transformation in newly developed DSSs at different deformation temperatures and strain rates.